Key conditions for Euroregions development at external EU borders: A case study of the Polish–Belarusian borderland. Issue 4 (21st April 2021) - Studzieniecki, Tomasz; Jakubowski, Andrzej; Meyer, Beata
Abstract: External borders of the European Union (EU) constitute a significant spatial and formal legal barrier for mutual relations. The key role in overcoming this barrier is played by cross‐border cooperation implemented by subnational units. The objective of this article is to identify key conditions for the cross‐border cooperation on the Polish–Belarusian border, constituting the external border of the EU. An additional objective is to develop a concept of institutionalization of the cross‐border cooperation, and to point to the possibilities of its implementation in the area of the Polish–Belarusian Euroregion Przybuże. This objective has been implemented by means of the triangulation method with the application of interrelated research techniques such as focus group interview, moderated workshop, surveys and desk research. The research discovered long‐term, intense cross‐border relations existing in the said region. The leaders of the cooperation were identified on both sides of the border. The institutionalization of this cooperation through the creation of the Euroregion was recognized by the stakeholders as an opportunity to dynamize social and economic development and to absorb EU funds more effectively. The developed concept of Euroregions creation and the case study analysis enrich the scientific output related to the theory of territorial cooperation, and offer practical solutions useful in the development of cross‐border areas, with particular consideration of regions located at the external borders of the EU. Abstract: 欧州連合(EU)の対外国境(external borders)は、相互関係のための重要な空間的、形式的な法的障壁を構築する。この障壁を克服する上で重要な役割を果たしているのは、国境を越えた協力であり、それを実施しているのが地方組織である。本稿の目的は、EUの対外国境であるポーランドとベラルーシの国境における国境協力のための重要な条件を明らかにすることであり、また、国境協力の制度化の概念を展開し、ポーランドとベラルーシの間のユーロリージョンにおける協力の可能性を指摘することである。この目的は、フォーカスグループインタビュー、モデレーテッドワークショップ、観測調査およびデスクリサーチのような相互に関連した研究技術を適用した三角測量法により実施した。その結果、その地域に長期的で強固な国境を越えた関係が存在することが見いだされた。その協力の指導者たちは国境の両側で確認された。ユーロリージョンの創造を通じたこの協力の制度化は、社会的・経済的発展を活性化し、EU資金をより効果的に吸収する機会として、ステークホルダーに認識された。ユーロリージョンの創造の概念とケーススタディの分析は、地域協力の理論に関連する科学的成果を豊かにし、特にEUの対外国境に位置する地域を考慮して、国境を越えた地域の開発に有用な実用的解決策を提供するものである。 Abstract: Las fronteras exteriores de la Unión Europea (UE) constituyen una importante barrera espacial y jurídica formal para las relaciones mutuas. El papel más importante para superar esta barrera lo desempeña la cooperación transfronteriza, llevada a cabo por las unidades subnacionales. El objetivo de este artículo es identificar las condiciones clave para la cooperación transfronteriza en la frontera polaco‐bielorrusa, que forma la frontera exterior de la UE. Un objetivo adicional fue desarrollar un concepto de institucionalización de la cooperación transfronteriza, y señalar las posibilidades de su aplicación en el área de la Eurorregión polaco‐bielorrusa Przybuże. Este objetivo se ha llevado a cabo mediante el método de triangulación, aplicando técnicas de investigación interrelacionadas como los grupos focales, el taller moderado, las encuestas y la investigación de gabinete. La investigación descubrió relaciones transfronterizas intensas que existen desde hace tiempo en dicha región. Los líderes de la cooperación fueron identificados a ambos lados de la frontera. La institucionalización de esta cooperación a través de la creación de la Eurorregión fue reconocida por las partes interesadas como una oportunidad para dinamizar el desarrollo social y económico y para atraer fondos de la UE con mayor eficacia. El concepto desarrollado de la creación de Eurorregiones y el análisis de estudios de caso enriquecen la producción científica relacionada con la teoría de la cooperación territorial y ofrecen soluciones prácticas útiles para el desarrollo de las zonas transfronterizas, con especial consideración de las regiones situadas en las fronteras exteriores de la UE.